Smartphone addiction and its effect on sleep quality in medical students - a cross-sectional study - Jain, Mudita; Kumar, Mohit; Gawande, Avinash; Narlawar, Uday; Padyal, Pratik (International Journal Of Community Medicine And Public Health, 2025)
Background: Individuals increasingly rely on their smartphones for communication, entertainment, and work, the boundaries between day and night seem to blur, leading to disrupted sleep patterns and reduced sleep quality. This cross-sectional study aims to investigate the relationship between smartphone addiction and sleep quality in medical students. Methods: A cross-sectional study was carried out among 228 undergraduate medical students in Nagpur from 01 May 2023 to 30 July 2023. Data were collected using universal sampling. A semi-structured proforma was used to obtain demographic details. Smartphone addiction scale-short version was used to assess smartphone addiction in the participants. Sleep quality was assessed using Pittsburgh's sleep quality index (PSQI). Data were analysed using Microsoft excel. Results: Among 228 medical students, 129 (56.58%) were addicted to smartphone usage and 162 (71.05%) used smartphone to access social media. There was no statistically significant gender difference in smartphone addiction (p=0.68). The PSQI revealed poor sleep quality in 158 (69.3%). Smartphone addiction was found to be statistically significantly associated with poor sleep quality (p<0.001). Conclusions: This cross-sectional study underscores the significant negative impact of smartphone addiction on sleep quality among medical students. Addressing this issue is crucial for promoting their well-being and academic success, necessitating interventions to cultivate healthy digital habits for improved sleep patterns.